Localized disruption of redox homeostasis boosting ferroptosis of tumor by hydrogel delivery system - Xiaomin Su (Elsevier, 2021)
Ferroptosis has received ever-increasing attention due to its unparalleled mechanism in eliminating resistant tumor cells. Nevertheless, the accumulation of toxic lipid peroxides (LPOs) at the tumor site is limited by the level of lipid oxidation. Herein, by leveraging versatile sodium alginate (ALG) hydrogel, a localized ferroptosis trigger consisting of gambogic acid (GA), 2,2′-azobis [2-(2-imidazolin-2-yl) propane] dihydrochloride (AIPH), and Ink (a photothermal agent), was constructed via simple intratumor injection. Upon 1064 ​nm laser irradiation, the stored AIPH rapidly decomposed into alkyl radicals (R•), which aggravated LPOs in tumor cells. Meanwhile, GA could inhibit heat shock protein 90 (HSP90) to reduce the heat resistance of tumor cells, and forcefully consume glutathione (GSH) to weaken the antioxidant capacity of cells. Systematic in vitro and in vivo experiments have demonstrated that synchronous consumption of GSH and increased reactive oxygen species (ROS) facilitated reduced expression of glutathione peroxidase 4 (GPX4), which further contributed to disruption of intracellular redox homeostasis and ultimately boosted ferroptosis. This all-in-one strategy has a highly effective tumor suppression effect by depleting and generating fatal active compounds at tumor sites, which would pave a new route for the controllable, accurate, and coordinated tumor treatments.